2015
DOI: 10.1590/1678-7205
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos do uso territorial por onça parda (Puma concolor), através de monitoramento via satélite, na região do Parque Estadual da Serra do Brigadeiro, MG

Abstract: RESUMOObjetivou-se com o presente estudo monitorar o comportamento do uso territorial de um macho de onça parda, capturado no Parque Estadual da Serra do Brigadeiro (PESB), por meio da telemetria, usando colar de GPS via Satélite Globalstar. O monitoramento de doze meses resultou na transmissão via satélite de 328 localizações, as quais sugerem que a área utilizada por esse felino seja de aproximadamente 610km 2 , sendo esta a maior área já descrita para a espécie. Foi possível observar que apenas 20% das loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
0
5
0
5
Order By: Relevance
“…Telemetry studies suggest that pumas (P. concolor) have extensive home ranges in various biomes (Paula et al 2015) and have been confirmed in 2 protected areas nearby (Duas Bocas Biological Reserve and Santa Lúcia Ecological Station). It is therefore possible that individuals of P. concolor are moving among these fragments.…”
Section: Discussionmentioning
confidence: 94%
“…Telemetry studies suggest that pumas (P. concolor) have extensive home ranges in various biomes (Paula et al 2015) and have been confirmed in 2 protected areas nearby (Duas Bocas Biological Reserve and Santa Lúcia Ecological Station). It is therefore possible that individuals of P. concolor are moving among these fragments.…”
Section: Discussionmentioning
confidence: 94%
“…Desse modo, sua ausência na área de estudo ainda não é compreendida. A ausência de P. concolor dentro do campus pode estar relacionada à sua baixa densidade populacional (Kelly et al 2008, Paula et al 2015) e à necessidade de grandes áreas de vida (> 10.000 ha; Sweanor et al 2000, Gonzalez-Borrajo et al 2017. Entretanto, Santos et al (2016) registraram dois indivíduos desta espécie em uma área de proteção ambiental de apenas 235 ha no município de Lavras, a cerca de 10 km de distância do campus da UFLA.…”
Section: Discussionunclassified
“…It has an area of 14,984 hectares, between the Meridian 42°20' and 42°40' W, and the parallels 20°20' and 21°00' S. Located in the Serra da Mantiqueira, its altitude ranges from 1,000 to 2,000 meters, with deep valleys and small plateaus that exert a significant influence on the climatic characteristics of the park. Its rainy period occurs between November and March, and its hottest, driest period is from April to September, with the quarter between June and August being the coldest (Paula et al, 2015). For this study, in addition to the park area, a buffer that extends one kilometer (15,134 hectares) from the limits of the UC was also included, totaling 30,118 hectares.…”
Section: Methodsmentioning
confidence: 99%